The Interpretation of Dreams and the Freudian Legacy in Contemporary Psychoanalysis (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
ABSTRACTThe article revisits Sigmund Freud’s The Interpretation of Dreams (1900), analyzing its relevance to contemporary psychoanalysis. Through a bibliographic review, the author examines Freud’s key concepts and their dialogue with neuroscience and cognitive psychology. The study concludes that Freud’s dream theory remains theoretically and clinically relevant.
Keywords: Freud; Interpretation of Dreams; Psychoanalysis; Unconscious; Neuropsychoanalysis.